The Development of Innovative CRM E-Commerce: The Case of Blibli.Com - Indra Gamayanto; Henry Christian (Binus Business Review, 2018)
This research discussed how e-commerce companies improve its competitiveness in the retail industry in Indonesia through innovative CRM. Blibli.com is one of the largest e-commerce companies in Indonesia that provides customers with innovative services to enhance its competitiveness with other e-commerce companies. This research also aimed to explore the strategies carried out by Blibli.com in developing its CRM. It used the 7s stages of McKinsey analytical methodology. The 7s stages of McKinsey was the excellent method of analyzing a company, regarding hard skills (Strategy, Structure, and System) and soft skills (Skill, Staff, and Style). This research finds that Blibli.com is an innovative CRM e-commerce. The analysis confirms that Blibli.com employs good strategies, structure, and system that lead to a competitive company. The company also provides training for its staffs, manages the staff and style properly. As a result, Blibli.com can widen its market, compete effectively with other e-commerce companies, and create a new market to gain big profits in the future.